Electrochemical surface activation of commercial tungsten carbide for enhanced electrocatalytic hydrogen evolution and methanol oxidation reactions - Ammar Bin Yousaf (17148391) (2022)
The chemistry of electrocatalysts deals with multiple critical factors to facilitate the electrochemical reactions. Among those, the rate limiting depends on electrons transfer for chemisorptions of molecules in redox reactions. This feature can be directly linked with efficient catalyst support material in electrocatalysis. To this end, we have developed a novel, simple and facile route to introduce commercially available material with tuned surface and interface chemistry for their potential applications in fuel cells (FCs) science and technology. Commercial tungsten carbide (WC) was activated by means of electrochemical oxygen reduction reactions (ORR) on different rotation rates to induce mild interactions of oxygen molecules with surface of WC at specified reduction potentials. The X-ray diffraction and X-ray photoelectron spectroscopy analysis before and after the activation confirmed the tuning of WC surface with incorporation of potential factors to activate them for enhanced electrocatalytic activities. In addition, the electrocatalytic methanol oxidation reactions (MOR) and hydrogen evolution reactions (HER) were carried and confirmed the exceptional boosted-up electrocatalytic behaviour of WC after the activation. The enhancement in electrocatalytic mechanism after activation was also tested and proved by means of in-situ FTIR spectroelectrochemical analysis for methanol electro-oxidation. In addition, the electrochemical depositions of Pt nanoparticles were carried out on WC surface before and after the activation to reveal the influence of surface activation for accommodating the foreign particles as support material in electrocatalysis. The results shown two fold enhancement in anodic performance of Pt-modified activated WC catalyst for methanol oxidation reactions and hydrogen evolution reactions in fuel cells. Other Information Published in: Journal of Electroanalytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jelechem.2022.116525